Factors that influence adolescents condom use decision-making in the Western Cape, South Africa - Davids, Eugene Lee (Department of Public Health and Family Medicine, 2020)
This study explores factors that influence condom use decision-making of adolescents from two schools in the Western Cape, South Africa. Thematic analysis was used to analyse the data generated from 16 individual semi-structured interviews. When exploring the factors that influence adolescent’s condom use decision-making, sexual debut and the role that emotion plays in the decision-making process were frequently discussed. The themes which emerged for sexual debut included relationships were about displaying true love which was equated with having sex and respecting parents’ expectations and rules informing decisions not to have sex at this age. When exploring the themes which emerged for condom use decision-making, the adolescents spoke about their concerns for the future and organising their lives. In addition, anticipated fear about falling pregnant, becoming parents and being infected with a disease emerged when exploring adolescent condom use decision-making. Understanding adolescent condom use can assist in aligning sexual and reproductive health (SRH) interventions and supporting healthy SRH decision-making and healthy relationships for adolescents.